The Influence of Leadership and Work Motivation on Cyberloafing Activities Among Personnel of the Mobile Brigade Unit of the Yogyakarta Special Region Police - Ananda Ariviana; Siswanto Siswanto (International Journal of Economics and Management Sciences, 2025)
This study aims to analyze the influence of leadership and work motivation on cyberloafing activities among mobile brigade personnel in the Special Region of Yogyakarta Regional Police. Specifically, the research examines: (1) the effect of leadership on cyberloafing, (2) the effect of work motivation on cyberloafing, and (3) the combined effect of leadership and work motivation on cyberloafing. The research employs an associative quantitative method with a sample of 247 mobile brigade personnel selected using probability sampling. Data collection was conducted through questionnaires and interviews, utilizing a Likert scale to measure responses. Before hypothesis testing, prerequisite analyses were carried out, including linearity, multicollinearity, autocorrelation, and heteroscedasticity tests. The main analytical technique applied was multiple linear regression.The results show that leadership has a positive and significant influence on cyberloafing activities, with a t-value of 2.764, significance level of 0.003 (<0.05), and a regression coefficient of 0.100. Similarly, work motivation also has a positive and significant influence on cyberloafing, with a t-value of 10.692, significance level of 0.004 (<0.05), and a regression coefficient of 0.440. Furthermore, simultaneous testing using the F-test reveals that leadership and work motivation jointly have a significant effect on cyberloafing, with an F-value of 67.412 and a significance of 0.000 (<0.05). The coefficient of determination (R²) obtained is 0.356, indicating that 35.6% of variations in cyberloafing activities can be explained by leadership and work motivation, while the remaining 64.4% is determined by other factors not examined in this study. These findings emphasize the importance of leadership approaches and motivation strategies in managing non-productive online behaviors within police organizations.